The Potential of Digital Storytelling as an Ethnographic Research Technique in Social Sciences - Oğuz Hatice Şule (Cultural Science, 2015)
By using ethnographic research techniques, we can ask questions in order to understandsome issues in the social sciences such as experience, the unique, the ordinary, daily life, emotions etc. However, it is possible to query the proficiency of current ethnographic techniques to design dialogic research and to convey the experiences of the ‘subjects’ of the field research. Techniques such as in-depth interviews, informal interviews and even the focus group depend on the dichotomy of the researcher who asks questions and the subject who responds to them. However, designing dialogic field research requires refusing those dichotomies, which can be considered to be inherited from a positivist understanding of science. In this article I discuss the potential of any digital storytelling workshop as an ethnographic research technique, with regard to three issues that seem problematic in current ethnographic techniques: integrated research processes; power and hierarchy relationships; and conveying the voice of subjects. The discussion of this article results from two academic experiences: One of them is my ethnographic field research experience for my doctoral dissertation; When I was writing my doctoral dissertation, entitled The Experience of Asylum Seeking in Turkey within the Context of Intercultural Communication, I conducted field research between 20 July and 20 December 2011, when I investigated how asylum-seeking in Turkey is experienced in daily life within the context of intercultural communication. In my field study, which lasted for five months in Gaziantep, one of the provinces that is located on the south-eastern part of Turkey, I adopted and put to use the participant observation, informal interview and in-depth interview techniques. I experienced a number of difficulties in conducting a field research with a sensitive (disadvantaged) group of people such as the asylum seekers. the other is the digital storytelling workshop entitled When I was in the field: Digital Stories from Young Academic Women . We conducted this workshop within the body of Hacettepe University, Faculty of Communication, between 25 March and 16 April 2013. I was one of the facilitators of the workshop. We had two purposes. The first was to share stories about our field research experiences as woman academicians. We wanted to understand if gender differentiates the field research experiences. The second was to use DST (digital storytelling) as an ethnographic research technique. We wanted to discuss the problems of ethnographic research techniques that we encounter in the field and see if DST has a potential that allows us to ask new questions. First, I discuss the weaknesses of current ethnographic research techniques and, second, I focus on how digital storytelling workshops can help to reduce these weaknesses. Finally, in conclusion, I touch on the discussions – carried out in the workshop mentioned above – regarding the opportunities and difficulties of using the digital stories and the workshop process as one of the ethnographic research techniques.